PRAKTIK DIFFERENTIATED INSTRUCTION MELALUI EXO-PJBL PADA MATERI BERKEMBANGNYA KEBUDAYAAN HINDU-BUDDHA UNTUK SISWA FASE E SMAN 7 MALANG - Laili, Vita Sabrina Azda (Jurnal Pendidikan Sejarah Indonesia, 2025)
The necessity for differentiated instruction in history learning is evident due to the diverse needs of learners in terms of interests, readiness, preferences, and intelligence. Implementing a learning model such as Exo-PjBL or Exhibition Project Based Learning can assist Phase E learners in achieving their goals within the context of the Merdeka Curriculum. The objective of this research is to describe and disseminate the various elements that differentiate the Exhibition Project Based Learning model. This will support the achievement of the aim of history education according to the applicable curriculum and train students to have 21st century skills, which are essential for individuals in the modern era. The research employs a descriptive qualitative method to elucidate how the Exo-PjBL model provides differentiated learning experiences to students and supports them in acquiring 21st century skills. The results of this study indicate that the Exo-PjBL model can facilitate the implementation of differentiated instruction (through differentiation of content, product, process, and learning environment elements) in learning Indonesian history for Phase E students at SMAN 7 Malang. This indicates that the benefits of the project-based learning model as well as differentiated instruction can be felt by students, especially in supporting the achievement of history learning objectives.